The Building Obe of Curriculum on Quality Assurance System of Accredited a Private Technical Study Program in Medan City - Dedi Amrizal; Yusriati Yusriati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this research to: 1) to find out data and information related to the commitment of higher education institutions in preparing their study programs to carry out international accreditation; 2) to find out the readiness of the study program in taking international accreditation; 3) to find out to what extent the preparation of the OBE curriculum has been developed by the study programs that will be prepared to carry out international accreditation.The research method used is descriptive method with data collection techniques using qualitative methods through an indept question approach. This research was conducted by using categorization analysis as a conclusion technique. Through this research, it has been found that the study programs at private universities in Medan have not prepared themselves well in order to face international accreditation. This can be seen from the implementation of OBE in SPMI that has not been implemented, so that the development of the OBE curriculum is also neglected. The main reason is the lack of commitment from the leaders of each university. The existence of national issues related to ongoing government programs is a top priority from the rectorate to the head of the study program. All preparation steps for international accreditation and all OBE curriculum development activities have not received serious attention.